2020
DOI: 10.1111/bju.15225
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic scoring system and risk stratification in patients with emphysematous pyelonephritis: an 11‐year prospective study at a tertiary referral centre

Abstract: Objectives To define pre‐morbid, clinical, laboratory, and imaging features and identify prognostic factors associated with morbidity and mortality in patients with emphysematous pyelonephritis (EPN) and develop a prognostic scoring system for improving management outcomes. Patients and Methods From January 2009 to December 2019, we performed a prospective study of all patients with a suspected diagnosis of EPN referred to a specialist tertiary centre in South India. All patients who underwent non‐contrast com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 30 publications
0
20
0
Order By: Relevance
“…This too focused more on mortality rates and was not externally validated. 11 The present work in this large cohort of patients with EPN attempts to identify the best approach to evaluating and triaging these critically sick patients, to expedite their care using MEWS, NEWS, SOFA, qSOFA and SIRS. In our study, all the predictive clinical scoring systems performed well, each achieving AUC > 0.7.…”
Section: Discussionmentioning
confidence: 99%
“…This too focused more on mortality rates and was not externally validated. 11 The present work in this large cohort of patients with EPN attempts to identify the best approach to evaluating and triaging these critically sick patients, to expedite their care using MEWS, NEWS, SOFA, qSOFA and SIRS. In our study, all the predictive clinical scoring systems performed well, each achieving AUC > 0.7.…”
Section: Discussionmentioning
confidence: 99%
“…PCN is part of the initial treatment in patients with emphysematous pyelonephritis [ 9 ]. The PCN was used in most of our patients to relieve obstruction (renal calculi, pregnancy-related hydronephrosis, and pyonephrosis) and obtain access to the renal system (removal of forgotten stents and percutaneous nephrolithotomy) [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the literature review, Chawla et al analyzed 90 consecutive patients and found that the NEWS scoring system was best able to predict the requirement of ICU care [24]. Krishnamoorthy et al described that the objective and qualitative risk stratification assessment is necessary for treating patients with EPN [25].…”
Section: Discussionmentioning
confidence: 99%